(untitled) (Per Musi, 2021)
The main objective of this article is to approach the concept of idiomatism in the context of classical guitar (violão) composition, through the analysis of works by guitarist composers who resorted to aspects of the construction and practice of the instrument as a primary vehicle for writing musical pieces. These composers, namely Heitor Villa-Lobos, Dilermando Reis, Garoto and Guinga, departing from the exploration of idiomatic possibilities of the instrument, developed a set of composition techniques that will be identified. The idiomatic elements we considered more significant explained the use of composition strategies based on the particularities of the instrument, and to identify not only musical elements such as scales, harmonic progressions and rhythms, but also other resources related to poetic, cultural, and communicative aspects of musical discourse.